2018
DOI: 10.1093/abm/kay040
|View full text |Cite
|
Sign up to set email alerts
|

Parental Expectation of Side Effects Following Vaccination Is Self-fulfilling: A Prospective Cohort Study

Abstract: Side effect perception following vaccination is influenced by psychological factors, in particular expectations. Perceiving side effects reduces future vaccination intention. Future public health communications should aim to decrease unrealistic expectations of side effects to increase vaccine uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
0
21
1
1
Order By: Relevance
“…Fear of side‐effects is one of the most commonly cited reasons for not adhering to medical interventions 9 . Side‐effect expectations have also been associated with decreased intention to adhere to medications 48 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fear of side‐effects is one of the most commonly cited reasons for not adhering to medical interventions 9 . Side‐effect expectations have also been associated with decreased intention to adhere to medications 48 .…”
Section: Discussionmentioning
confidence: 99%
“…While other research has focused on the negative role of the media on side‐effect reporting, 104,105 one study included in the review found that consulting newspapers as a source of information was associated with decreased side‐effect expectations 52 . Research has indicated that side‐effect expectations mediate the association between increased suggestion of side‐effects from different sources, and later perception of side‐effects 9 . It is therefore important to quantify the role of suggestions from different sources such as online searches, social media, news and the influence of friends, family and health‐care practitioners across different treatments for different illnesses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These impacts motivate the study of factors that support vaccine uptake. Undervaccination may be attributed to vaccine refusal 2 , the spread of anti-vaccine opinion facilitated by media coverage and its sensationalisation of true adverse vaccine effects 3 , the expectation of adverse effects 4 , misstatement of the cause of illnesses 5 , the spread of other rumours and false information 6 , and the effect of social norms 7 .…”
Section: The Resurgence Of Infectious Diseases Due To Vaccine Refusalmentioning
confidence: 99%
“…Each items reflected VH using the agreement of the responses. Meanwhile, specific questions of the reason for vaccination or hesitation were structured with references [6,18-20]. Items asked the reason for hesitating, delaying, or refusing vaccination; the person who made impacts; and the reason for ultimately vaccinating.…”
Section: Methodsmentioning
confidence: 99%